Totally implantable venous access port insertion via open Seldinger approach of the internal jugular vein—a retrospective risk stratification of 500 consecutive patients - Becker, Felix (Langenbecks Arch Surg, 2021)
PURPOSE: Modern oncological treatment algorithms require a central venous device in form of a totally implantable venous access port (TIVAP). While most commonly used techniques are surgical cutdown of the cephalic vein or percutaneous puncture of the subclavian vein, there are a relevant number of patients in which an additional strategy is needed. The aim of the current study is to present a surgical technique for TIVAP implantation via an open Seldinger approach of the internal jugular vein and to characterize risk factors, associated with primary failure as well as short- (< 30 days) and long-term (> 30 days) complications. METHODS: A total of 500 patients were included and followed up for 12 months. Demographic and intraoperative data and short- as well as long-term complications were extracted. Primary endpoint was TIVAP removal due to complication. Logistic regression analysis was used to analyze associated risk factors. RESULTS: Surgery was primarily successful in all cases, while success was defined as functional (positive aspiration and infusion test) TIVAP which was implanted via open Seldinger approach of the jugular vein at the intended site. TIVAP removal due to complications during the 1st year occurred in 28 cases (5.6%) while a total of 4 (0.8%) intraoperative complications were noted. Rates for short- and long-term complications were 0.8% and 6.6%, respectively. CONCLUSION: While the presented technique requires relatively long procedure times, it is a safe and reliable method for TIVAP implantation. Our results might help to further introduce the presented technique as a secondary approach in modern TIVAP surgery.